Boston 2025 - Vorhees, Mara; Heller, Carolyn B. (Lonely Planet city guide., 2025)
"Lonely Planet's Boston is our most comprehensive guide that extensively covers all the city has to offer, with recommendations for both popular and lesser-known experiences. Explore Boston's revolutionary history, feast on sensational seafood and catch a game at Fenway Park; all with your trusted travel companion"--Publisher's description.